(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Traumatic brain injury is a significant public health problem. Objective: This study was aimed to clinical characteristics of traumatic brain injury patients by collection of detailed data on demography, clinical, injury patterns, co-morbidities, laboratory findings, and outcome of mild and moderate TBI. Methodology: This cross-sectional study was conducted from September 2019 to June 2020. Patients attending Department of Trauma Neurosurgery of National Institute of Neurosciences & Hospital, Dhaka, Bangladesh and Department of Neurosurgery of Dhaka Medical College Hospital, Dhaka, Bangladesh with a history of having mild or moderate traumatic brain injury and patients of 18 years and above irrespective of their sex were included in the study after informed written consent. The study included socio-demographic information and history of injury, mechanism of injury, information of physical examination, clinical features including cognitive change and co-morbidities were recorded. Results: A total number of 210 patients were included in this study. Motor vehicle related accident was 56.2% cases. About 21.4% cases of them were assaulted (physically), 12.9% cases of them were fall from the height. About 58.0% patients were normal cognition; 22.0% cases were mild cognitive impairment; 17.6% cases were moderate cognitive impairment and only 2.0% cases were severe cognitive impairment during discharge. Glasgow Coma Scale (GCS) during admission after resuscitation around 78.0% cases were moderate head injury and 22.0% cases were mild head injury. About 47.14% patients had single or multiple cerebral hemorrhagic contusion; 13.8% patients had traumatic subarachnoid hemorrhage; 8.6% cases had thin layer of subdural hematoma; 6.2% cases had epidural hematoma; Conclusion: Traumatic brain injury patients have mostly due to road traffic accidents and are presented with cerebral hemorrhagic contusion, subarachnoid hemorrhage and subdural hematoma Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):105-111